An empirical analysis of the (Un)readability of inmate handbooks - Krienert, Jessie L. (Journal of crime and justice, 2024)
All 50 state Departments of Corrections (DOC) provide some form of handbook to inmates upon their incarceration. Handbooks specify, in part, the rules, regulations, responsibilities, and consequences of behavior critical for upholding safety, security, and order within correctional institutions. Considering the vital importance of these documents to the inmate and the institution, it is essential they be written at a level accessible and understandable to incarcerees. The present multi-method study first assessed the purpose of inmate handbooks. Qualitative results suggest handbooks serve as informational guides regarding the facility’s rules. Moreover, a significant portion of the handbooks emphasize that inmates bear the responsibility of understanding and adhering to the instructions outlined in the provided guide. Next, quantitative analysis of 74 inmate handbooks from DOCs in 49 US states was completed, utilizing three established readability metrics (the Flesch Readability Scale, the Flesch-Kincaid Grade Level, and the SMOG index), to determine whether handbooks are suitably written for their intended inmate audience. All 74 reviewed handbooks significantly exceeded a reasonable expectation of readability given the likely literacy and education levels of inmates. Recommendations are provided for the improvement of inmate handbook readability drawing on the empirical findings of the present study.